Pengaruh Dukungan Sosial dan Perbandingan Sosial terhadap Kesejahteraan Subjektif Ibu Muda Pengguna Media Sosial - Agustiani, Syahra; Gazi, Gazi (TAZKIYA Journal of Psychology, 2021)
This research was conducted to determine the influence of social support (emotional support, instrumental support, informational support, and companionship support), social comparison (opinion and ability) and age among young mothers who use social media. A sample of 200 young mothers aged 18-37 years was taken with non-probability sampling techniques. This research used Satisfaction with Life Scale (SWLS) & Positive Negative Affect Schedule (PANAS) to measure the subjective well-being variable. The instrument for social support was arranged based on theory of Sarafino (2011). Futhermore the instrument for social comparison was modified from the Iowa-Netherlands Comparison Orientation Scale (INCOM). The results showed there was a significant influence of social support, social comparison, and age towards subjective well-being of young mothers. The minor hypothesis test of four dimensions of social support showed only one dimension that influenced subjective well-being, which was emotional support. On social comparison, one of the two dimensions that significantly influenced subjective well-being was ability, whereas the other dimension which was opinion did not give significant influence toward subjective well-being.